'The body is a tool for remembrance'. (24th July 2022) - Sijapati, Megan Adamson
Abstract : This article is a preliminary analysis of the role of the body in core rituals of a North American branch of the Shadhilyya Sufi order. It draws upon fieldwork conducted between 2016 and 2020 to consider how spiritual healing practices involve the human body sensorily and in experiential, imaginative realms, as conveyed through practitioners' verbal descriptions of what they feel in the body and how they understand their bodies and the bodies of others. I demonstrate how, in these healing practices, the body is instrumentalized in three key modes – as barometer, controller, and ground of energy – that change the way it is experienced. I argue that the 'ordinary' – or, non-extraordinary – body is instrumentalized through these healing modalities to become the site of transformation from spirit to material and material to spirit, and that through this the body emerges as central to everyday, lived Sufi practice. The healings discussed incorporate traditional Muslim devotional practices and long-standing Islamic and Sufi rituals such as dhikr (remembrance, recollection of the divine), recitation of the 99 names of the divine, Qur'anic recitation, cupping, and less traditionally Islamic practices such as acupuncture.